DATA MODEL CUSTOMIZATION FOR YII BASED ERP APPLICATION - Leander, Andre; Wibowo, Adi; Dewi, Lily Puspa (Institute of Research and Community Outreach - Petra Christian University, 2014)
As UD. Logam Utama’s business grow, trigger the need of fast and accurate information in order to improve performance, efficiency, control and company’s values. The company needs a system that can integrate each functional area. ERP has centralized database and able to be configured, according to company’s business processes.First phase of application development is analysis and design the company’s business processes. The design phase produce a number of models that will be used to created application.The final result of application development is an ERP application that can be configured with the company’s business process. The ERP application consist of warehouse or production module, purchasing module, sales module, and accounting module.